Gly-Val-Arg, an angiotensin-I-converting enzyme inhibitory tripeptide ameliorates hypertension on spontaneously hypertensive rats - Manoharan, Sivananthan; Shuib, Adawiyah Suriza; Abdullah, Noorlidah; Ashrafzadeh, Ali; Kabir, Nurul (Elsevier, 2018)
The tripeptide GVR was previously shown to inhibit ACE and was able to reduce systolic blood pressure in SHRs within 6 h after administration. To further analyse the potential of tripeptide GVR in lowering blood pressure, a long term study was carried out where the tripeptide was orally administered to SHRs for 21 days. Elevated systolic blood pressure was significantly reduced when the peptide was administered at 50 mg/kg body weight and 100 mg/kg body weight. Body weight of the SHRs did not change significantly between the studied groups and the histopathological findings indicated that there were no abnormalities in liver and kidney tissues. From the acute toxicity analysis of this tripeptide, using the Up and Down method revealed that the peptide was non-toxic to SHRs. Tripeptide GVR demonstrated endothelium-dependent vasorelaxation activity using thoracic aortas from SD rats in which vasorelaxation was not observed in denuded aortas. The metabolomic analysis carried out from the sera of SHRs demonstrated changes on metabolites associated with pathways related to renin angiotensin system. As for proteomic analysis, differentially expressed proteins detected were mainly proteins related with inflammation. Based on the results, tripeptide GVR has a potential to ameliorate the elevated blood pressure in SHRs.